Development of WO3-Gd2O3˗ B2O3 high density glasses doped with Dy3+ for photonics and scintillation materials application - N. Wantana (2020)
© 2020 Elsevier Masson SAS The Dy3+ ions doped tungsten gadolinium borate (Dy-WGdB) glasses were synthesis by the melt-quenching technique with various Dy2O3 concentrations. The physics, optical and several types of luminescence properties in the Dy-WGdB glass samples were researched. Glass densities (~6.0 g/cm3) indicates that the compaction of glass is high and rise with an increment of Dy2O3 concentrations. The Dy-WGdB glass samples absorb photons in visible light (VIS) and near-infrared (NIR) region from the absorption spectra. For photo-, radio- and proton luminescence, the highest emission was observed at 575 nm, corresponding to Dy3+ transition 4F9/2 → 6H13/2. The maximum concentration of Dy2O3 doped in the WGdB glass is 1.0 mol%, which has achieved the highest emission intensity in all three types of luminescence. For 1.0 mol% doped glass, the decay times under pulse X-ray excitation was measured and found to be 0.216 ms. The temperature dependent luminescence spectra of the 1.0% doped glass in a temperature range, 10 K–300 K was measured and found the thermal quenching. In this research, under the photo, X-ray and proton excitation, the WGdB glass doped with Dy2O3 displays the strong luminescence in the VIS region. It has the potential for applications in high-energy and nuclear physics, radiation control and homeland security.